Partial sequence analysis of 130 randomly selected maize cDNA clones. - Keith, C S (1993)
As part of a project to identify novel maize (Zea mays L. cv B73) genes functionally, we have partially sequenced 130 randomly selected clones from a maize leaf cDNA library. Data base comparisons revealed seven previously sequenced maize cDNAs and 18 cDNAs with sequence similarity to related maize genes or to genes from other organisms. One hundred five cDNAs show little or no similarity to previously sequenced genes. Our results also establish the suitability of this library for large-scale sequencing in terms of its large insert size, proper insert orientation, and low duplication rate.